Analisis Spasial Karakteristik Lingkungan dan Dinamika Kepadatan Anopheles sp. Pengaruhnya terhadap Kejadian Malaria di Kecamatan Seram Barat Kabupaten Seram Bagian Barat Maluku - Watmanlusy, Efraim; Raharjo, Mursid; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2019)
Latar belakang: Kecamatan Seram Barat merupakan salah satu wilayah di bagian timur Indonesiayang endemis malariadan dikategorikan tinggi dengan indikator API diatas angka nasional. Angka kesakitan malaria per 1000 penduduk pada tiga tahun terakhir fluktuatif dimana API tahun 2014 (22,8‰), 2015(6,147‰) dan 2016 (9,03‰) dengan441kasus klinis,248kasus positif, ditemukan 23 spesies namun belumterkonfirmasi sebagai vektor malaria.Tujuan : Menganalisis secara spasial karakteritik linkungan dan dinamika kepadatan Anopheles sp. pengharunya terhadap kejadian malaria di Kecamatan Seram Barat.Metode : Jenis Penelitian ini adalah observasional analitik, desainnyacross sectionalyang pelaksananya di Kecamatan Seram Barat terhadap 100 orang yang dipilih secara purposive sampling. Pengumpulan data melalui wawancara, observasi  dan Penangkapan nyamuk dengan metode upan orang didalam dan di halaman rumah. Analisis data menggunakan uji chi-square.Hasil :Hasil penelitian ditemukan 41 reponden positif malaria, 5 spesies Anopheles sp. yakni An.vagus, An.teselaltus, An.kochi, An.barbirotris, An.farautidan tidak terkonfirmasi sebagai vektor malaria, variabel yang mempengaruhi kejadian malaria adalah Suhu udara (p= 0,022, PR = 2,082), Kelembaban (p= 0,003, PR = 3,421),Kepadatan Anopheles sp. (p=0,001, PR = 2,853), Jarak Breeding places (0,000, RP= 10,054). Kesimpulanadalahtedapat 41 kasus, 5 spesies Anopheles sp. Suhu udara, kelembaban, kepadatan Anopheles sp, jarak breeding placesmempengaruhi kejadian malaria, tidak ditemukan Anopheles sp sebagai vektor malaria di Seram Barat berdasakan hasil uji PCR ABSTRACTTitle: Spatial Analysis of Environmental characteristics and Dynamics of Density Anopheles sp. As The Effect on Malaria Case in West Seram District, Western Area of Seram Regency, Maluku.Background: West Seram District is one of the regions in eastern Indonesia that became malaria endemic area and categorized as high with the API indicator above the national figure. The number of malaria morbidity, per 1000 of population, had been fluctuating in last three years which shown by API in 2014 (22.8 ‰), 2015 (6,147 ‰) and 2016 (9.03 ‰) with 441 clinical cases, 248 positive cases, 23 species have been found but it has not been confirmed yet as a malaria vector. The purpose of the study is to analyze spatially the characteristics of the environment and the dynamics of the density from Anopheles sp. as the effect on the case of malaria in West Seram District.Methods: the type of this research is boservational analytic with cross sectional design. The research was held in West Seram District toward 100 people that were selected by purposive sampling.The collecting data had been done through interview, observation, and catching the mosquitoes using bait people method inside and outside the house yard. The analysis were using chi-square test.Result : The results of the study found 41 respondents positive for malaria, 5 species of Anopheles sp. namely An.vagus, An.teselaltus, An. kochi, An. barbirotris, and An. farauti. The variables affecting the case of malaria were air temperature (p = 0.022, PR = 2.082), humidity (p = 0.003, PR = 3.421), density of Anopheles sp. (p = 0.001, PR = 2,853), breeding places distances (0,000, RP = 10,054). The result of PCR test shows that there are no species containing Plamodium were found. Conclusion;The result detected  41 cases, identified 5 species of Anopheles sp. air temperature, humidity, density of Anopheles sp, distance of breeding places affecting the case of malaria. There are no Anopheles sp were found as a malaria vector in Seram Barat based on PCR test result.